2018
DOI: 10.1136/bjophthalmol-2017-311234
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab for the treatment of refractory active and inactive non-infectious uveitis

Abstract: Adalimumab appears to reduce the corticosteroid burden in active and inactive non-infectious uveitis in the real-world setting. Inflammatory activity at the time of adalimumab commencement may determine long-term treatment success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 24 publications
2
34
0
Order By: Relevance
“…Notably, our study showed that ADA is effective also in the long-term follow-up, with more than 90% of the patients with ocular control over a median follow-up of 36 months. Our findings on the long-term ADA control is of importance for clinicians, considering that all other studies had a significantly shorter follow-up [1, 6, 8, 1113, 16].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Notably, our study showed that ADA is effective also in the long-term follow-up, with more than 90% of the patients with ocular control over a median follow-up of 36 months. Our findings on the long-term ADA control is of importance for clinicians, considering that all other studies had a significantly shorter follow-up [1, 6, 8, 1113, 16].…”
Section: Discussionmentioning
confidence: 76%
“…Compared with other retrospective studies, our work included a considerably larger cohort of cases. In particular, Dobner et al [11] evaluated ADA treatment in 60 patients, Durrani et al [12] in 32 patients, and Lee et al [13] in 22 patients. Studies with a larger population were the trials [1, 8], but as compared to the VISUAL-1 and 2 populations, our cohort was mainly composed of subjects with a concomitant systemic inflammatory disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no TNFi are currently licensed to treat AAU in adults, although adalimumab is licensed to treat non-infectious intermediate, posterior and panuveitis. 6 In a post hoc analysis of randomised controlled trials for axSpA and other conditions, as well as in many observational studies, it has been shown that monoclonal TNFi are efficacious in AAU, with monoclonal antibody TNFi showing superior efficacy over etanercept. 7– 9…”
Section: Introductionmentioning
confidence: 99%
“…Their outcomes are excellent and similar to those reported previously by our group and others. 6,7 Castle and Gale refer to another article in the November issue by Olver et al, that discusses ethical decision-making in healthcare resource allocation. 8 We have no argument with the sound principles espoused and agree completely on the importance of an ethical, inclusive, accountable and transparent process for healthcare resource allocation.…”
Section: Author Replymentioning
confidence: 99%